Augmented reality for advanced prosthetic training in non-amputees - Lauren Deus; Leah Wohlbach; Susan E. D’Andrea (PLoS ONE, 2026)
Prosthetic abandonment is highly prevalent among upper extremity amputees (UEA), partly due to lack of engaging and motivating training to use their devices. Augmented reality (AR) systems can be used for rehabilitation, and are advantageous because they offer stimulating, goal-oriented experiences for participants to immerse themselves in while performing repetitive tasks to improve function. Thus, in this study, the effects of a novel AR prosthetic training game, and the transfer of skills to a functional rehabilitation performance assessment involving tasks of daily living were investigated. Thirty-two able-bodied participants, sixteen allocated to receive AR training and sixteen received no training, donned a bypass body-powered prosthetic device to engage in a functional task assessment, evaluated at two time points. The AR group used the bypass prosthesis to engage in the AR training game, ARm-Strong, on each of three training sessions. AR group participants completed a questionnaire at the end of the intervention to evaluate their feelings on the AR game. On average, individuals in the AR group were significantly more efficient at using the bypass prosthesis to complete functional tasks compared to the control group, however, the rate of improvement was similar between groups. Individuals who engaged in the AR training felt positive feelings of engagement, engrossment, and immersion towards the application although the impression of immersion was significantly less than that of engagement and engrossment. The results of this study support previous findings that AR training is an engaging and motivating experience, and motor learning can be achieved through this type of training. Future implications of the results may benefit prosthesis users by enhancing user experience during prosthetic training and ultimately lead to better rehabilitation and overall adherence to the use of the prosthetic device.